2006
DOI: 10.1111/j.1365-2478.2006.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated geological and geophysical exploration for concealed ores beneath cover in the Chaihulanzi goldfield, northern China

Abstract: A B S T R A C TAn integrated geological and geophysical investigation was carried out in the near-mine areas of the Chaihulanzi gold-field, Inner Mongolia, northern China, to determine the south-eastern strike extension of the principal mineralized shear system, in the search for new resources. In this case study, surface geophysical surveys played an important role in defining the mineralized structures beneath cover. A re-investigation of the mine geology by observing the underground exposures of mineralizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This system uses both natural and man-made electromagnetic signals to obtain a continuous electrical sounding of the earth beneath the measurement site. The details are given by Geometrics and EMI ElectroMagnetic Instruments (2000) and Liu et al (2006) . Because Ex and Ey dipole sizes and the betweenstation distance (BSD ) should be changed according to the scales and geometries of the objects detected, we determined measurement sites at 20 m MN with 10 m Ex and Ey dipole sizes in order to obtain clear results.…”
Section: Stratagem Eh4 Systemmentioning
confidence: 99%
“…This system uses both natural and man-made electromagnetic signals to obtain a continuous electrical sounding of the earth beneath the measurement site. The details are given by Geometrics and EMI ElectroMagnetic Instruments (2000) and Liu et al (2006) . Because Ex and Ey dipole sizes and the betweenstation distance (BSD ) should be changed according to the scales and geometries of the objects detected, we determined measurement sites at 20 m MN with 10 m Ex and Ey dipole sizes in order to obtain clear results.…”
Section: Stratagem Eh4 Systemmentioning
confidence: 99%
“…Where AMT signal levels are low, e.g., in the dead band at $ 800-3000 Hz (Garcia and Jones 2002), the controlled-source audiomagnetotelluric method (CSAMT, f = 1-10000 Hz, Zonge and Hughes 1991) is routinely applied. Consequently, MT methods have a long-standing history in the investigation of mineral deposits (Strangway et al 1973;Meju 2002;Jones 2017) with field cases reported from, for instance, copper, gold, lead, silver and zinc deposits (Kellett et al 1993;Garcia Juanatey et al 2013a, b;Hübert et al 2013;Hu et al 2013), copper, gold and iron deposits (Heinson et al 2006), copper and iron deposits (Chouteau et al 1997;Jones and Garcia 2003), copper, iron and zinc deposits (Basokur et al 1997), copper, lead and zinc deposits (Sasaki et al 1992;Bastani et al 2009), copper and nickel deposits (Lakanen 1986;Livelybrooks et al 1996;Jones et al 1997;Balch et al 1998;Stevens and McNeice 1998;Zhang et al 1998;Watts and Balch 2000;King 2007;Xiao et al 2011;Varentsov et al 2013; Le et al 2016a), copper, silver and zinc deposits (Gordon 2007), gold deposits (Jones et al 1997;Liu et al 2006;Howe et al 2014;Takam Takougang et al 2015;Hübert et al 2016;Le et al 2016b), and uranium deposits (Leppin and Goldak 2005;Tuncer et al 2006;Farquharson and Craven 2009;Goldak et al 2010;…”
Section: Mt Methods In Exploring Deep Ore Depositsmentioning
confidence: 99%
“…The application of VLF method for cost effective imaging and detection of near surface targets for prospection of ore deposits has been in use for over 10 years; some of examples include Eze et al (2004), Frasheri et al (1995), Hutchinson and Barta (2002), Ligas and Palmoba (2006), Liu et al (2006), McCaffrey et al (1995, Paterson and Ronka (1971), and Saydam (1981). Bayrak (2002) applied the VLF method to chrome area to inspect the effectiveness of the method.…”
Section: Introductionmentioning
confidence: 99%